Penyelesaian Sengketa dalam Hukum Kontrak: Tinjauan Literatur Tentang Proses Arbitrase dan Mediasi - Putra Dirgantara; Heigel Parodi Ritonga (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Dispute resolution in contract law is a crucial aspect of maintaining harmonious business relationships. Two commonly used alternative mechanisms are arbitration and mediation. This article aims to review the literature discussing the effectiveness of these mechanisms in resolving contractual disputes. Through a literature review method, this study examines various relevant academic sources from the last five years. The findings indicate that arbitration offers higher legal certainty, whereas mediation is more flexible and allows for more creative solutions and better relationships between parties. This study provides insights for legal practitioners and academics in understanding the advantages and disadvantages of each dispute resolution method.